Draft Genome Sequence of the Sulfobacillus thermosulfidooxidans Cutipay Strain, an Indigenous Bacterium Isolated from a Naturally Extreme Mining Environment in Northern Chile - Travisany, Dante (American Society for Microbiology, 2012)
Sulfobacillus thermosulfidooxidans strain Cutipay is a mixotrophic, acidophilic, moderately thermophilic bacterium isolated from mining environments of the north of Chile, making it an interesting subject for studying the bioleaching of copper. We introduce the draft genome sequence and annotation of this strain, which provide insights into its mechanisms for heavy metal resistance.